Dynamic and distributional effects of environmental revenue recycling schemes: Simulations with a general equilibrium model of the Italian economy - Roberto Roson (Fondazione Eni Enrico Mattei (FEEM), 2002)
A dynamic general equilibrium model of the Italian economy is used to assess the impact of carbon taxation (or auctioned carbon permits), where additional revenue is used to cut either existing taxes on labour or on capital income. Simulation results do not support the existence of the so-called "double dividend" when labour taxes are reduced, whereas lower tax rates on capital have mild positive effects on growth and welfare, with progressivity properties on income distribution. These findings hinge on the assumptions of open economy, given world interest rate, and capital mobility.
Keywords: 330; Applied general equilibrium models; double dividend; environmental taxation; Italy; Ökosteuer; Einkommensverteilung; Dynamisches Gleichgewicht; Italien; Doppelte Dividende